Development of partial model-based torque control of AC induction motors. - Dong Sun (IEEE Transactions on robotics and automation)
A partial model-based torque control algorithm is developed for AC induction motors. The motor is regarded as a torque source, and a desired torque signal is designed based on the desired position trajectory. A reference quadrature axis current input is further developed to cause the torque to track the designed torque signal, utilizing a torque feedforward plus a PI-type torque feedback control. The method utilizes partial knowledge of the electromechanical dynamic model of the induction motor. Experiments conducted on a commercial AC induction servo system demonstrate the validity of the proposed approach